Agenda de contatos em sistema web com sincronização via web service para celulares com sistema operacional Android - Queiroz, Altieres Herculano Bianchi de (2011)
This work presents a survey of tools for handling personal contacts (address books) using mobile smartphones. The main applications available at the brazilian market are listed, and their key features are highlighted. Some foreign tools are also evaluated. This work also proposes a new applications, for Android based mobile phones, that allows the user to export/import its personal contacts to/from a webbased system, also developed by the author. The communication is achieved through Web Services, using the Java Web Service specification. A working prototype, involving the Android application, the web-based system, and the communication protocol, is presented, and is capable of storing user data on the web server, making it available to the user via an web interface, for consult, update and management. The Android application developed allows synchronization, so in case of loss of the mobile phone, the contacts are preserved and can be downloaded for a new mobile phone. Besides that, the developed system also allows the automatic update of the contacts phone numbers, if authorized by other users using the system, providing a kind of "social network” for personal phone contacts.